The Impact of Substance Use Disorders On Women Involved in Dependency Court - Holly A. Hills; Deborah Rugs; M. Scott Young (Washington University Journal of Law & Policy, 2004)
Women are entering substance abuse treatment in increasing numbers and, often, come to treatment as the result of their involvement in dependency court. Unfortunately, traditional substance abuse treatment models are not designed to address women with children and multiple vulnerabilities. Part I of this Essay reviews the literature and data discussing the relationship between child abuse and neglect and substance abuse. Part II identifies referral pathways through which women enter substance abuse treatment, focusing on the referral process in the Hillsborough County, Florida dependency courts. Part III describes the role of dependency courts in encouraging compliance with substance abuse treatment recommendations. Part IV identifies innovative substance abuse treatment models that address women and their children. Part V describes the methodology and findings of key informant interviews and file reviews, which were conducted to uncover the complex issues associated with women involved in substance abuse treatment as a result of abuse or neglect charges. Finally, Part VI provides recommendations to better address the substance use disorders of women involved in dependency court.
Keywords: Pregnant women -- Substance use; Domestic relations courts